Factors Analysis Affecting Low Productivity in High-Rise Building Projects in Surabaya City - Aileen Indonesia; I Putu Artama Wiguna (Institut Teknologi Sepuluh Nopember (ITS), 2024)
High-rise building construction projects are characterized by significant risks andnumerous challenges, which frequently lead to low productivity, causing delaysand hindering project completion. One way to address these problems is to analyzethe risk factors of low productivity in construction projects using a clusteringmethod based on their probability and impact. This approach helps determine thedominance level of each cluster and provides insights into the occurrence of riskfactors that affect low productivity in high-rise building projects in Surabaya City.This research was conducted with surveys filled out by 37 respondents involvedin four high-rise building projects in Surabaya City. The aim of this study is toanalyze risk factor clustering and determine the dominance of each clusteraffecting low productivity in high-rise building projects in Surabaya City byemploying the Agglomerative Hierarchical Clustering method to identify clustersand determine the most dominant cluster using Euclidean Distance. From theliterature review, 33 risk factors were identified as the variables of this research.The AHC method was carried out based on the mean probability and impact ofeach cluster obtained from the survey. The result of AHC is that Cluster 1 consistsof 23 factors, Cluster 2 consists of 5 factors, and Cluster 3 consists of 5 factors.For the dominance level of each cluster, the Euclidean distance method wascarried out, and the result was that Cluster 2 emerged as the highest overall risk,and Cluster 3 represented a low overall risk.